2014
DOI: 10.4187/respcare.02559
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Smoking Cessation in Subjects With Cancer: A 30-Year Review

Abstract: BACKGROUND: Despite the established causal relationship between tobacco smoking and cancer, many cancer patients continue to smoke after diagnosis. This partly reflects ignorance of the beneficial effects of smoking cessation, even after diagnosis. The aim of this study was to demonstrate the effects of continuing or quitting smoking in patients with diagnosed cancer. METHODS: The study was based on a review of medical databases (PubMed Central, MEDLINE, Cochrane Library) in the last 30 y. All articles include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 46 publications
1
40
0
1
Order By: Relevance
“…Similar to other studies, smoking was associated with a high prevalence of analgesic use [41, 46, 47]. This could be due to the fact that smoking is strongly associated with having more pain [48, 49]. We also observed a significant association between obesity and consuming more prescribed analgesics.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to other studies, smoking was associated with a high prevalence of analgesic use [41, 46, 47]. This could be due to the fact that smoking is strongly associated with having more pain [48, 49]. We also observed a significant association between obesity and consuming more prescribed analgesics.…”
Section: Discussionsupporting
confidence: 89%
“…A recent study reported that, similar to depression, greater daily pain ratings were associated with lower likelihood of cessation attempts and greater use of nicotine among cancer patients [Aigner, 2016]. Additionally, continued smoking following a cancer diagnosis was associated with higher levels of pain among cancer patients, compared to former and non-smokers [Daniel, 2009; Florou, 2014]. Previous research studies have identified tobacco addiction to be a risk factor for chronic pain among general population [Shiri, 2010; Sugiyama, 2010].…”
Section: Unique Clinical Aspects and Challenges For Cancer Patientsmentioning
confidence: 99%
“…Smoking cessation carries numerous benefits, even after a cancer diagnosis, including a greater response to cancer treatment [1, 9, 10] and reduced risk of mortality [1, 3, 9]. Cancer survivors who continue to smoke are at a higher risk than non-smoking survivors for secondary primary cancers as well as a wide range of other conditions causally associated with smoking, including diabetes, cardiovascular disease, impaired iimnune function, rheumatoid arthritis, dental disease, pain-related impairment, and more [1, 11]. Given the large population of cancer survivors who smoke and the importance of smoking cessation in tins population, a critical need exists to understand both the barriers and facilitators of smoking cessation in tins very high risk population, particularly since conventional behavioral and pharmacologic smoking cessation programs are not effective at increasing the smoking cessation in cancer survivors [12].…”
Section: Introductionmentioning
confidence: 99%